The Post-Crisis Growth Slowdown in Emerging Economies and the Role of Structural Reforms - Qureshi, Zia; Diaz-Sanchez, Jose L.; Varoudakis, Aristomene (World Bank Group, Washington, DC, 2014)
This paper constructs indicators of structural bottlenecks arising from barriers to open markets, obstacles to business operations, and constraints to access to finance. Empirical evidence from a sample of 30 emerging economies indicates that barriers to open markets and access to finance are significantly associated with differences in total factor productivity growth in the post-global financial crisis period compared with the pre-crisis period -- with countries with fewer barriers showing stronger recovery and resilience. Barriers to access to finance are also associated with differences in the performance of private investment. Reforms to improve the policy framework in these areas, up to the level of the best-ranking countries, could offset the recently observed growth slowdown in emerging economies. These reforms would revitalize potential growth and mitigate the risks from external shocks associated with the global environment in the transition from the global financial crisis.